Adaptation of a PTSD intervention for use in primary care in a low-income country: The Brief Relaxation, Education and Trauma HEaling intervention for Ethiopia (BREATHE Ethiopia) - Lauren C. Ng; Gray K. Bowers; Dagmawit Tesfaye; Eyerusalem Getachew Serba; Abebaw Fekadu; Kimberly Hook; Amantia Ametaj; David C. Henderson; Kim T. Mueser; Charlotte Hanlon (SSM - Mental Health)
Posttraumatic Stress Disorder (PTSD) symptoms amongst people with serious mental illness (SMI) are prevalent in Ethiopia and throughout the world, yet treatment is scarce, particularly in low-resource settings with few mental health providers. This study describes the process of adapting a PTSD treatment, originally designed to be delivered by mental health providers in specialty mental health clinics in the US, to be appropriate, acceptable and sustainable when delivered by non-specialist providers in routine care in rural Ethiopian primary care clinics. Methods included a literature review, qualitative interviews (N = 48), an adaptation workshop (N = 12), and theater, cognitive, and usability testing (N = 14) with people with SMI, caregivers of people with SMI, health care providers, and community leaders. Participants found the intervention to be appropriate and acceptable, while also noting multiple patient, family, provider, clinic and community-level barriers that might impact successful delivery and receipt of the intervention. The intervention was adapted to address as many barriers as possible, while maintaining adherence to the original intervention's theoretical and conceptual model. While many of these barriers could be addressed with adaptations, others such as high rates of poverty and limited population-level mental health awareness, require policy and community-based solutions and systemic change. Future research is needed to assess whether the intervention is feasible and effective in this setting.